Survival probability of the ancestors of the indigenous people of Canada who migrated during the last glacial maximum - Nagasaki, Kibo; Nagasak, Shinya (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this study is to examine the survival probability of the ancestors of the indigenous people of Canada during their migration to the last glacial maximum. The ancestors of the Indigenous people of Canada are believed to have migrated during the Last Glacial Maximum under severe ice-age conditions. However, the possibility of their survival is unclear. Creating a mathematical model, the survival probability of Indigenous ancestors who migrated to Canada and the effects of different factors were studied. Using logistic regression analysis, we evaluated the effects of different factors, such as the mean female life expectancy, average childbirth interval, and marriage age, on their survival probability. The results suggested that a polygamous community was more likely to survive. The survival probability was maximized in the cases of monogamy/unintentional migration (0.60), polygamy/unintentional migration (0.87), and marriage age of 15 years/monogamy/unintentional migration (0.76). However, the survival probability was low for many possible combinations of the mean female life expectancy and the average childbirth interval. The low survival probability would demonstrate the levels of resourcefulness, bravery, and wisdom that the Indigenous ancestors possessed to survive. A problem was that the available data on mortality and fertility were not specific to the ancestors of the Indigenous people of Canada. In the future, the accuracy of the survival probability of the ancestors of the Indigenous people of Canada will improve once quantitative research data on the ancestors’ life expectancy and childbirth are available.